Новый вид рода Gymnodactylus Spix, 1825 (Reptilia, Sauria, Gekkonida) из Пакистана - Голубев, М.Л.; Щербак, Н.Н. (Вестник зоологии, 1981)
Gymnodactylus mintoni Szczerback and Golubev, sp. n. is described from one specimen labelled 683 SAM & ad., Udigram in Swat, Pakistan, March 30 (year?) Coll. S .A. Minton (Indianapolis,Indiana, USA). Digits compressed, angularly bent, clearly shorter than in other Gymnodactylus species; the 4th toe has less than 20 subdigital lamellae. Dorsal tubercles smooth, small, not arranged into longitudinal rows, but sometimes irregular transverse rows may be seen;these tubercles areabsent on the dorsal tail surface. A row of enlarged subcaudal shields are absent. For intact animal colour and pattern see Minton, 1966 (as G. stoliczkai). The characters given above allow exact distinguishing the new gecko from all other species occurring within the region, including the similar G. chitranensis.